Parallels and discrepancies between non-native species introductions and human migration - Ahmed, Danish A; Sousa, Ronaldo; Bortolus, Alejandro; Aldemir, Ceray; Angeli, Nicole F; Błońska, Dagmara; Briski, Elizabeta; Britton, J Robert; Cano-Barbacil, Carlos; Clark-Ginsberg, Aaron; Culic, Irina; Cuthbert, Ross N; et al. (Biological reviews of the Cambridge Philosophical Society, 2025)
Biological invasions and human migrations have increased globally due to socio-economic drivers and environmental factors that have enhanced cultural, economic, and geographic connectivity. Both processes involve the movement, establishment, and spread of species, yet unfold within fundamentally different philosophical, social and biological contexts. Hence, studying biological invasions (invasion science) and human migration (migration studies) presents complex parallels that are potentially fruitful to explore. Here, we examined nuanced parallels and differences between these two phenomena, integrating historical, socio-political, and ethical perspectives. Our review underscores the need for context-specific approaches in policymaking and governance to address effectively the challenges and opportunities of human migration and harm from biological invasions. We suggest that approaches to studying the drivers of biological invasions and human migration provide an excellent opportunity for transdisciplinary research; one that acknowledges the complexities and potential insights from both fields of study. Ultimately, integrating natural and social sciences offers a promising avenue for enriching the understanding of invasion biology and migration dynamics while pursuing just, equitable, and sustainable solutions. However, while human migration is a clear driver of biological invasions, drawing on principles from biological invasions to understand past and current human migration risks oversimplification and the potential for harmful generalisations that disregard the intrinsic rights and cultural dynamics of human migrations. By doing so, we provide insights and frameworks to support the development of context-specific policies that respect human dignity, foster cultural diversity, and address migration challenges in ways that promote global cooperation and justice. This interdisciplinary approach highlights the potential for transdisciplinary research that acknowledges complexities in both fields, ultimately enriching our understanding of invasion biology and migration dynamics while pursuing equitable and sustainable solutions.
Keywords: zavlečené druhy; cultural assimilation; ecological resilience; biosecurity; globalisation; sociopolitical dynamics; Animals; ethnocentrism; Humans; transdisciplinary research; Introduced Species; lidé; Human Migration; zvířata; migrace lidstva